2004
DOI: 10.1002/mrm.10714
|View full text |Cite
|
Sign up to set email alerts
|

dGEMRIC (delayed gadolinium‐enhanced MRI of cartilage) indicates adaptive capacity of human knee cartilage

Abstract: Delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) is a new imaging technique to estimate joint cartilage glycosaminoglycan content by T 1 -relaxation time measurements after penetration of the hydrophilic contrast agent Gd-DTPA 2-. This study compares dGEMRIC in age-matched healthy volunteers with different levels of physical activity: Group 1 (n ‫؍‬ 12): nonexercising individuals; Group 2 (n ‫؍‬ 16): individuals with physical exercise averaging twice weekly; Group 3 (n ‫؍‬ 9): male elite runners. dGEMRIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 48 publications
11
119
1
3
Order By: Relevance
“…These include correspondence of the dGEMRIC index to cartilage 'softening' as seen by arthroscopy (199), correlation of the dGEMRIC index with the level of physical activity (200), improved differentiation of disease relative to radiography in individuals with hip dysplasia (201), discriminatory power of dGEMRIC in radiographically similar compartments of the knee (202), sensitivity of medial/lateral dGEMRIC to malalignment in the knee (202), lower dGEMRIC values in individuals with ACL injury (203) and sensitivity to changes in knee cartilage following posterior cruciate ligament (PCL) injury (204).…”
Section: Cross-sectional and Longitudinal Observations In Oamentioning
confidence: 99%
“…These include correspondence of the dGEMRIC index to cartilage 'softening' as seen by arthroscopy (199), correlation of the dGEMRIC index with the level of physical activity (200), improved differentiation of disease relative to radiography in individuals with hip dysplasia (201), discriminatory power of dGEMRIC in radiographically similar compartments of the knee (202), sensitivity of medial/lateral dGEMRIC to malalignment in the knee (202), lower dGEMRIC values in individuals with ACL injury (203) and sensitivity to changes in knee cartilage following posterior cruciate ligament (PCL) injury (204).…”
Section: Cross-sectional and Longitudinal Observations In Oamentioning
confidence: 99%
“…Many studies have shown that mechanical loading of articular cartilage affects the metabolism of chondrocytes and its biochemical composition [1,32,37]. Both animal and human studies have shown that the GAG content is higher in cartilage that is habitually loaded [19,33] or has a higher level of activity [39], whereas immobilization results in a reversible decrease in cartilage PG content [18,30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the MRI studies were performed at a field strength of 9.4 T, which is substantially larger than the typical clinical field strengths of 1.5 or 3 T. We note that successful FCD measurements have nonetheless been carried out at these lower field strengths. 3,31,32 Finally, while the present results provide strong evidence of the utility of MRI in monitoring the development of FCD in injectable hydrogel constructs, the effectiveness of this approach remains to be established in in vivo studies. 33 We note that the present investigation was targeted to the specific hypothesis that noninvasive MRI measurements of FCD would correlate with biochemically determined GAG in developing neocartilage.…”
mentioning
confidence: 67%